The Role of Changes Political Geography to Directing Political Diplomacy and war : (2000-1162 B.C) - Ari Khalil Kamil; Cheman Raqib Fateh (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Political geography has been reflected in the political and security situation of the kings and ruling states in second millennium B.C, and in light of the criteria of distance and proximity to borders and importance as well as the time dimension, it is possible to define the political relations between kings and sages , in an attempt by them to establish diplomatic relations with the existence of conflicts and attacks or to take the neutral side in these wars for the purpose of protecting their supreme interests and protecting the security of the country, of course the wars, conflicts and diplomatic relations were reflected in the political events of the distant and bordering countries, as we find between the Kingdom of Eshnunna and Assyria and the Kingdom of Larsa with Essen and Babylon And the Kassites with the Elamites, and so on.., and it is worth noting that the kings, for the sake of their political interests and the protection of their borders, established diplomatic relations with their neighboring countries in order to maintain the balance of power and prevent the establishment or building state, such as relation between Mitannians with the Eighteenth Dynasty in Egypt against Hittites , when the latter began to improve its relations. If the complexities of political problems have a direct impact on relations, whether or not there is continuity.